Morphological Features of Human Cerebellar Cortex in Old Age - Irina A Balandina (Journal of Global Pharma Technology, 2017)
The objective of the study is to establish regularities of age changes in the structural organization of thecerebellar cortex in old age as compared to young age by using necropsy material. Craniometrical,organometric, histological, immunomorphological and morphometric studies of the cerebellar cortex in219 human corpses (108 men and 111 women) aged from 18 to 44 years and from 75 to 90 years.Comparative analysis of the parameters of Purkinje’s cells in these age groups revealed a decrease in theneurons’ height and width. It was found that the distance between the bodies of the neurons of ganglioniclayer increases with age, which is obviously due to the progressing disorganization and apoptotic death ofPurkinje’s cells. An increase in the number of astrocytes immunopositive to glial fibrillary acidic protein,S-100 protein and vimentin in the granular and molecular layers of the cerebellar cortex is observed, aswell as a decrease in the number of Purkinje’s cells immunopositive to neuron-specific enolase andimmunonegative to S-100 protein and vimentin, which can be considered as a manifestation ofneurodegeneration. Immunohistochemical techniques provide a more differentiated approach to themorphological assessment of the cerebellar cortex in old persons and make it possible to get moreobjective and complete information about the postnatal morphogenesis.